Expression of a fungal cyanamide hydratase in transgenic soybean detoxifies cyanamide in tissue culture and in planta to provide cyanamide resistance - Zhang, Xing-Hai (Journal of plant physiology, 2005)
Embryogenic tissue cultures of soybean were transformed by particle bombardment with a vector pCHZ-II that carries the coding sequence for cyanamide hydratase (Cah), an enzyme that converts toxic cyanamide to urea, from the soil fungus Myrothecium verrucaria. The Cah gene was driven by the constitutive Arabidopsis thaliana actin-2 promoter and terminated with its cognate terminator. This vector also carries the hygromycin phosphotransferase gene (hpt) driven by the potato (Solanum tuberosum) ubiquitin-3 promoter. Twelve individual lines of transgenic plants that were obtained under hygromycin selection expressed Cah mRNA and exhibited resistance to hygromycin in leaf tissue culture, while the untransformed tissues were sensitive. Cah enzyme activity was present in extracts of transformed leaves and embryogenic tissue cultures when measured by a colorimetric assay and the presence of the Cah protein was confirmed by enzyme-linked immunosorbent assay (ELISA). Cah expression detoxified cyanamide in leaf callus and embryogenic cultures as well as in whole plants as shown by cyanamide resistance. The Cah-expressing plants grew and set seeds normally indicating that the Cah enzyme activity did not affect soybean plant metabolism. We also describe a test whereby callus was formed on cultured leaf tissue in the presence of hygromycin or cyanamide only if the hpt or Cah gene was expressed, respectively. This test is a convenient and cost-effective way to follow the marker gene in the primary regenerated plants and subsequent generations, which is particularly reliable for the hpt gene expression using hygromycin